Impact of Early Life Stress on Reward Circuit Function and Regulation - Hanson, Jamie L.; Williams, Alexia V.; Bangasser, Debra A.; Peña, Catherine J. (Frontiers in Psychiatry, 2021)
Early life stress – including experience of child maltreatment, neglect, separation from or loss of a parent, and other forms of adversity – increases lifetime risk of mood, anxiety, and substance use disorders. A major component of this risk may be early life stress-induced alterations in motivation and reward processing, mediated by changes in the nucleus accumbens (NAc) and ventral tegmental area (VTA). Here, we review evidence of the impact of early life stress on reward circuit structure and function from human and animal models, with a focus on the NAc. We then connect these results to emerging theoretical models about the indirect and direct impacts of early life stress on reward circuit development. Through this review and synthesis, we aim to highlight open research questions and suggest avenues of future study in service of basic science, as well as applied insights. Understanding how early life stress alters reward circuit development, function, and motivated behaviors is a critical first step toward developing the ability to predict, prevent, and treat stress-related psychopathology spanning mood, anxiety, and substance use disorders.